High-performance solid-state cooling materials: Balancing magnetocaloric and non-magnetic properties in dual phase La-Fe-Si. (15th February 2017) - Shao, Yanyan; Liu, Jian; Zhang, Mingxiao; Yan, Aru; Skokov, Konstantin P.; Karpenkov, Dmitriy Yu; Gutfleisch, Oliver
Abstract: La(Fe, Si)13 H-based materials are considered to be one of the most promising room-temperature magnetic refrigerants. The intrinsic brittleness and relatively low thermal conductivity in La-Fe-Si-H alloys, however, have severely hindered its preparation, shaping and application. To solve this long-standing problem, in this work we propose a novel approach to fabricate stable La-Fe-Si-H blocks and plates by adding extra α-Fe as a reinforcing phase to enhance mechanical integrity. Much better bending strength compared to that in the stoichiometric composition has been observed in our dual phase La-Fe-Si-H magnetic refrigerants. Such novel Fe-rich plates can be exposed to 10 5 magnetic field cycles without losing mechanical integrity. In addition, a large and reproducible Δ T ad of 5.4 K in 1.93 T and a thermal conductivity of 6 W/mK at room temperature have been obtained. Graphical abstract: In the dual phase La-Fe-Si-H alloys, materials can be fabricated to the block shape, where the toughening α-Fe guarantees the mechanical integrity and offers significantly enhanced thermal conductivity. Image 1